2021
DOI: 10.3390/molecules26071982
|View full text |Cite
|
Sign up to set email alerts
|

Biological Effects of β-Glucans on Osteoclastogenesis

Abstract: Although the anti-tumor and anti-infective properties of β-glucans have been well-discussed, their role in bone metabolism has not been reviewed so far. This review discusses the biological effects of β-glucans on bone metabolisms, especially on bone-resorbing osteoclasts, which are differentiated from hematopoietic precursors. Multiple immunoreceptors that can recognize β-glucans were reported to be expressed in osteoclast precursors. Coordinated co-stimulatory signals mediated by these immunoreceptors are im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 118 publications
1
4
0
Order By: Relevance
“…These findings suggested that Ps-GOS has a suppressive effect on not only osteoclast multinucleated cell formation but also their bone resorption ability. As demonstrated previously, S. cerevisiae β-glucan may have an inhibitory effect on bone resorption in the in vivo animal models [31].…”
Section: Discussionsupporting
confidence: 54%
“…These findings suggested that Ps-GOS has a suppressive effect on not only osteoclast multinucleated cell formation but also their bone resorption ability. As demonstrated previously, S. cerevisiae β-glucan may have an inhibitory effect on bone resorption in the in vivo animal models [31].…”
Section: Discussionsupporting
confidence: 54%
“…β-Glucan, which is part of the S. cerevisiae cell wall, contributed to the downregulation of receptor activator for nuclear factor κB ligand (RANKL) and the upregulation of OPG, which resulted in the inhibition of bone loss in a mouse model. 113 The suppressive activity of β-glucan derived from baker’s yeast against RANKL has also been demonstrated by Hara et al 114 Stimulation of mouse bone marrow cells with S. cerevisiae β-glucan inhibited differentiation from maturing osteoclasts by downregulating the nuclear factor of activated T cells 1 (NFATC1), which was caused by the suppression of NF-κB signaling and c-fos expression. 114 β-Glucan can not only inhibit osteoclast activity but also be used as a polymer when designing biocomposites modified with a ceramic phase.…”
Section: Biomolecules Used For Bone Regenerationmentioning
confidence: 82%
“…There is substantial scientific evidence to conclude that polycan, a β-glucan derived from Aureobasidium pullulans , reduces the number of active osteoclasts and inhibits the secretion of pro-osteolytic cytokines such as interleukin-1β (IL-1β) and tumor necrosis factor-α (TNF-α). β-Glucan, which is part of the S. cerevisiae cell wall, contributed to the downregulation of receptor activator for nuclear factor κB ligand (RANKL) and the upregulation of OPG, which resulted in the inhibition of bone loss in a mouse model . The suppressive activity of β-glucan derived from baker’s yeast against RANKL has also been demonstrated by Hara et al Stimulation of mouse bone marrow cells with S. cerevisiae β-glucan inhibited differentiation from maturing osteoclasts by downregulating the nuclear factor of activated T cells 1 (NFATC1), which was caused by the suppression of NF-κB signaling and c-fos expression .…”
Section: Biomolecules Used For Bone Regenerationmentioning
confidence: 94%
See 1 more Smart Citation
“…In this work, composite membranes made of βg-PUL and PUL were built using βg and PUL, while glucan served as a plasticizer. 86 The resulting films’ properties and principles were expressed in the creation of βg-PUL composite films.…”
Section: Microspheresmentioning
confidence: 99%